Fabrication of ZnO nanowire device using top-down approach - Mohamed Sultan, Suhana (IEEE Explorer, 2011)
ZnO nanowire devices were fabricated from top-down using optical lithography. The nanowires are formed from anisotropic etch of 100 nm Filtered Cathodic Vacuum Arc (FCVA) deposited ZnO thin film. The nanowires are characterized using SEM and Raman spectroscopy via image mapping. The current-voltage characteristics showed a typical ohmic behaviour after contact annealing, reflecting the influence of the lowering of contact barriers between the ZnO nanowire device and the Al metal electrode.